Preparation method of formicary-shaped carbon material and zinc-iodine soft package battery

By preparing ant nest-like carbon material as the positive electrode material of zinc-iodine soft-packed batteries, the problem of low iodine load in the positive electrode material of zinc-iodine battery is solved, and the energy density and safety of the battery are improved.

CN119390054AActive Publication Date: 2025-02-07WUHAN UNIV OF SCI & TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411559094.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-02-07
Estimated Expiration
2044-11-04

AI Technical Summary

Technical Problem

The iodine loading in the positive electrode material of zinc-iodine batteries is not high, and existing soft-pack batteries have difficulty in improving safety and energy density.

Method used

By preparing ant nest-like carbon material, ZIF-8 is used to calcinate in a high-temperature argon atmosphere to obtain carbon material with a high specific surface area and a rich pore structure, as the positive electrode material for zinc-iodine soft-packed batteries, and water-based electrolyte and graphite paper are used. Current collector.

Benefits of technology

Improves the payload of iodine and the cycling performance of the material, enhances the energy density and safety of the battery, and avoids the risk of combustion or explosion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119390054A_ABST
    Figure CN119390054A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of aqueous batteries, and discloses a preparation method of an ant nest-shaped carbon material and a zinc-iodine soft package battery. The preparation method comprises the following steps: (1) preparing a ZIF-8 material from zinc nitrate hexahydrate and 2-methylimidazole; (2) calcining the material prepared in the step (1) to obtain an ant nest-shaped carbon material; the zinc-iodine soft package battery comprises a zinc foil negative electrode, an ant nest-shaped carbon material positive electrode, a glass fiber diaphragm and an electrolyte, the obtained ant nest-shaped carbon material has a high specific surface area and a rich pore structure, can effectively bear and limit an iodine active substance, and improves the effective utilization rate of an iodine simple substance; the dissolution and diffusion of intermediate product polyiodide ions can be limited, and the shuttle effect is inhibited; the price is low, the preparation method is simple and convenient, and the repeatability is high; and the aqueous electrolyte and the graphite paper current collector are adopted, so that dangerous conditions such as combustion or explosion and the like are not easy to occur. And meanwhile, the application of the graphite paper current collector shows the trend of increasing the energy density.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of aqueous batteries, in particular to a method for preparing an ant nest-shaped carbon material and a zinc-iodine soft-pack battery. Background Art

[0002] With the rapid development of portable electronic devices, electric vehicles and energy storage systems, higher requirements are placed on the energy density and safety of batteries. Zinc-iodine batteries have attracted widespread attention due to their high theoretical specific capacity, high safety, ideal redox potential, abundant resource reserves and low cost.

[0003] However, zinc-iodine batteries still have problems such as poor iodine conductivity and the shuttling effect of poly-iodine ions. The key lies in the effective adsorption and fixation of iodine by the positive electrode material. In order to solve these problems, researchers have developed a variety of iodine carrier materials, among which carbon materials have become ideal candidates for iodine carrier materials due to their high conductivity, strong plasticity and easy access. Although the research on zinc-iodine battery carrier materials has achieved a series of remarkable results, there are still some problems that need to be solved, such as the difficulty in increasing the actual capacity and the difficulty in increasing the iodine loading. Summary of the invention

[0004] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a method for preparing an ant nest-shaped carbon material and a zinc-iodine soft-pack battery to solve the problem that the iodine loading in the positive electrode material of the zinc-iodine battery is not high and the existing soft-pack batteries are difficult to improve in terms of safety and energy density.

[0005] To achieve the above object, the present invention is implemented through the following technical solutions:

[0006] In a first aspect, the present invention provides a method for preparing an ant nest-shaped carbon material, the preparation method comprising:

[0007] (1) mixing zinc salt and organic ligand in a solvent, stirring or standing at room temperature to synthesize ZIF-8;

[0008] (2) calcining the ZIF-8 prepared in step (1) at high temperature in an argon atmosphere to obtain an ant nest-like carbon material.

[0009] Further, the zinc salt is zinc nitrate hexahydrate; the organic ligand is 2-methylimidazole; the solvent includes water and methanol; the room temperature is 25 degrees Celsius;

[0010] Furthermore, in step (1), the zinc salt is 1-4 moles; the organic ligand is 4-8 moles; and the solvent volume is 200-500 ml.

[0011] Further, the zinc salt and the organic ligand in the molar ratio of 1:4 in step (1) are respectively added to 200-500 ml of methanol, stirred at room temperature at a stirring speed of 500-1000 rpm for 8-12 hours, the prepared product is collected by filtration, washed with methanol 3-5 times, and freeze-dried overnight to finally obtain ZIF-8 powder.

[0012] Further, in step (2), the ZIF-8 prepared in step (1) is heated to 900-1000 degrees Celsius at a heating rate of 2-3 degrees Celsius / minute under an argon atmosphere and calcined for 1-4 hours to obtain an ant nest-shaped carbon material. Appropriate calcination temperature and calcination time enable the material to have a better pore structure, which is beneficial to the storage of iodine in zinc-iodine batteries.

[0013] Further preferably, in step (2), the heating rate is 3 degrees Celsius per minute, and the temperature is raised to 950 degrees Celsius;

[0014] Furthermore, a zinc-iodine soft-pack battery, the preparation method of which comprises the following steps

[0015] Step (1): Mix the above-mentioned ant nest-shaped carbon material and iodine in a mass ratio of (1:1)-(1:1.5) in a high-pressure reactor, and react in a blast oven at 100-140 degrees Celsius for 2-6 hours for iodine sealing. After the reaction is completed, take the powder and dry it at 130 degrees Celsius for 1 hour to remove the residual iodine on the surface, and obtain the iodine-sealed ant nest-shaped carbon material. The iodine loading calculation formula of the material is: iodine loading = (mass of the ant nest-shaped carbon material after iodine sealing - mass of the initial ant nest-shaped carbon material) / (mass of the initial ant nest-shaped carbon material + iodine);

[0016] Step (2): LA133 type water-based adhesive and deionized water are dissolved in a mass ratio of 3:97, and stirred at high speed for 1-2 hours to prepare glue solution 1 at a stirring speed of 800 rpm;

[0017] Step (3): the superconducting carbon black and the iodine-sealed ant nest-shaped carbon material are mixed and ground evenly, and then added to the prepared glue solution 1, and stirred at a high speed for 1-2 hours to obtain a mixture 1, and the stirring speed is 1500 rpm;

[0018] Step (4): by adding an appropriate amount of deionized water, the viscosity of the mixture 1 is adjusted to 1500-2000 MPa.S and the fineness is 15 um to obtain a zinc-iodine battery positive electrode slurry;

[0019] Step (5): The zinc-iodine battery positive electrode slurry is evenly coated on the cut graphite paper current collector, and dried. After the coating is completed, a zinc-iodine battery positive electrode sheet is obtained. The electrode sheet has a width of 60 mm, a length of 70 mm, and an iodine mass of 20-30 mg.

[0020] Step (6): Winding the positive electrode sheet and the negative zinc sheet of the zinc-iodine battery with the glass fiber separator in a positive and negative relative manner into a soft-pack battery core, and covering the core with a finishing glue;

[0021] Step (7): Assemble with the aluminum-plastic film that has been pre-punched to a specified depth and cut, and perform top sealing and side sealing to form an unfilled soft-pack battery cell;

[0022] Step (8): injecting 1.3 ml of an electrolyte containing 2 mol zinc sulfate and 0.05 mol potassium iodide into the unfilled soft-pack battery cell, pre-sealing the top and side edges, and forming a liquid-filled soft-pack battery;

[0023] Step (9): The liquid-filled soft-pack battery is left to stand for a while until the electrolyte is fully infiltrated to form a zinc-iodine soft-pack battery.

[0024] Furthermore, the mass ratio of the LA133 aqueous adhesive in step (2), the superconducting carbon black in step (3), and the iodine-sealed ant nest-shaped carbon material is 7:2:1.

[0025] Furthermore, in step (7), the aluminum-plastic film is divided into two parts, the tank area and the air bag area; the thickness of the aluminum-plastic film is 150um; the tank area is formed into a pit shape with one side open by punching a hole on one side. The tank area is divided into two upper and lower grooves, which are folded in half and used to place the soft-pack battery cells. The depth of the two grooves is consistent with the thickness of the soft-pack battery cells; the air bag area uses an aluminum-plastic film with the same specifications and materials as the battery tank, which is a planar structure with the same size as the plane projection size of the battery tank, and is used to contain the gas generated during the battery formation process.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] 1. The present invention obtains an ant nest-shaped carbon material by adjusting the heating rate and the calcination temperature. The carbon material has a high specific surface area and a rich pore structure, can effectively carry and limit iodine active substances, and improve the effective utilization rate of iodine element; and the porous structure can limit the dissolution and diffusion of the intermediate product polyiodide ions and inhibit the shuttle effect; it can effectively improve the specific capacity of the material and its cycle performance.

[0028] 2. Zinc-iodine soft-pack batteries use aqueous electrolytes and graphite paper current collectors. Graphite paper has excellent high temperature resistance and thermal conductivity. The highest operating temperature can reach 400°C, and the maximum in-plane thermal conductivity can reach 1500W / mK. The thermal resistance is 40% lower than that of aluminum and 20% lower than that of copper. This makes it difficult for soft-pack batteries to be burned or exploded. Even in the case of severe local heating, large-scale short circuits or temperature runaway explosions will not occur, avoiding the risk of fire when the soft-pack battery is damaged, and increasing the safety characteristics of zinc-iodine soft-pack batteries.

[0029] 3. Zinc-iodine soft-pack batteries use graphite paper as current collectors, which is 30% lighter than aluminum of the same size and 80% lighter than copper. The use of graphite paper current collectors can significantly reduce the weight of the battery and increase the energy density of the soft-pack battery; in addition, the capacity of the soft-pack battery monomer can be increased by increasing the number of pole pieces, thereby further enhancing the energy density. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is a scanning electron microscope image of the ant nest-shaped carbon material prepared in Example 1 of the present invention;

[0031] Figure 2 This is the nitrogen adsorption-desorption curve of the ant nest-shaped carbon material prepared in Example 1 of the present invention;

[0032] Figure 3 This is a scanning electron microscope image of the carbon material prepared in Comparative Example 1 of the present invention;

[0033] Figure 4 This is the nitrogen adsorption-desorption curve of the carbon material prepared in Comparative Example 1 of the present invention;

[0034] Figure 5 This is a scanning electron microscope image of the carbon material prepared in Comparative Example 2 of the present invention;

[0035] Figure 6 This is the nitrogen adsorption-desorption curve of the carbon material prepared in Comparative Example 2 of the present invention;

[0036] Figure 7 The cyclic voltammetry test curve of the zinc-iodine button battery prepared in Application Example 1 of the present invention;

[0037] Figure 8 The constant current charge and discharge curve of the zinc-iodine button battery prepared in Application Example 1 of the present invention;

[0038] Fig. 9 The cycle curve of the zinc-iodine button battery prepared in Application Example 1 of the present invention;

[0039] Fig.10 The cyclic voltammetry test curve of the zinc-iodine button battery prepared in Application Example 2 of the present invention;

[0040] Fig.11 The cycle curve of the zinc-iodine button battery prepared in Application Example 2 of the present invention;

[0041] Fig.12 The cyclic voltammetry test curve of the zinc-iodine button battery prepared in Application Example 3 of the present invention;

[0042] Fig.13 The cycle curve of the zinc-iodine button battery prepared in Application Example 3 of the present invention;

[0043] Fig.14 The cyclic voltammetry test curve of the zinc-iodine button battery prepared in Application Example 4 of the present invention;

[0044] Fig.15 The cycle curve of the zinc-iodine button battery prepared in Application Example 4 of the present invention;

[0045] Fig.16 The cyclic voltammetry test curve of the zinc-iodine button battery prepared in Application Example 5 of the present invention;

[0046] Fig.17 This is an optical photograph of the soft-pack battery prepared in Example 4 of the present invention;

[0047] Fig.18 This is the constant current charge and discharge curve of the soft-pack battery prepared in Example 4 of the present invention;

[0048] Fig.19 This is a comparison chart of the energy density of the soft-pack battery prepared in Example 4 of the present invention versus the number of cycles.

[0049] Fig. 20 This is a temperature comparison diagram of the soft-pack battery prepared in Example 4 of the present invention during the discharge process with the traditional soft-pack battery. DETAILED DESCRIPTION

[0050] In order to make the technical means, creative features, purpose and efficacy of the present invention easy to understand, the present invention is further explained below in conjunction with specific embodiments. All raw materials in the present invention are not particularly limited to their sources, and can be purchased on the market or prepared according to conventional methods well known to those skilled in the art; there is no particular limitation on their purity, and the present invention preferably adopts the conventional purity used in the field of analytical purity or composite materials. The following is an explanation of the embodiments of the present invention by specific specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied by other different specific embodiments, and the details in this specification can also be based on different viewpoints and applications, without departing from the spirit of the present invention. Various modifications or changes are made. It should be noted that, in the absence of conflict, the features in the following embodiments and embodiments can be combined with each other.

[0051] Embodiment 1:

[0052] A method for preparing an ant nest-shaped carbon material, the preparation method comprising:

[0053] (1) dissolving 1 mol of zinc nitrate hexahydrate and 4 mol of dimethylimidazole in 200 ml of methanol, stirring and reacting at room temperature for 12 hours, collecting the prepared product by filtration, washing it with methanol three times, and freeze-drying it overnight to finally obtain ZIF-8 powder;

[0054] (2) 0.5 g of ZIF-8 prepared in step (1) was heated to 950 degrees Celsius at a heating rate of 3 degrees Celsius per minute under an argon atmosphere and calcined at 950 degrees Celsius for 4 hours to obtain an ant nest-shaped carbon material.

[0055] Figure 1 This is a scanning electron microscope image of the carbon material prepared in Example 1 of the present invention. From the image, it can be seen that the material presents a structure similar to an ant nest.

[0056] Figure 2 This is the nitrogen adsorption-desorption curve of the carbon material prepared in Example 1 of the present invention. The specific surface area of ​​the material is 1101.7 m2 / g, and it is mainly composed of micropores. The rich specific surface area and narrow mesopores are conducive to the adsorption of iodine in the carbon material.

[0057] Embodiment 2:

[0058] A method for preparing an ant nest-shaped carbon material, the preparation method comprising:

[0059] (1) Dissolve 1 mol of zinc nitrate hexahydrate and 4 mol of dimethylimidazole in 200 ml of methanol, stir and react at room temperature for 12 hours, collect the prepared product by filtration, wash it with methanol three times, and freeze-dry it overnight to finally obtain ZIF-8 powder.

[0060] (2) 0.5 g of ZIF-8 prepared in step (1) was heated to 900 degrees Celsius at a heating rate of 3 degrees Celsius per minute under an argon atmosphere and calcined at 900 degrees Celsius for 4 hours to obtain an ant nest-shaped carbon material.

[0061] Embodiment 3:

[0062] A method for preparing an ant nest-shaped carbon material, the preparation method comprising:

[0063] (1) Dissolve 1 mol of zinc nitrate hexahydrate and 4 mol of dimethylimidazole in 200 ml of methanol, stir and react at room temperature for 12 hours, collect the prepared product by filtration, wash it with methanol three times, and freeze-dry it overnight to finally obtain ZIF-8 powder.

[0064] (2) 0.5 g of ZIF-8 prepared in step (1) was heated to 1000 degrees Celsius at a heating rate of 3 degrees Celsius per minute under an argon atmosphere and calcined at 1000 degrees Celsius for 4 hours to obtain an ant nest-shaped carbon material.

[0065] Comparative Example 1

[0066] This comparative example provides a method for preparing a carbon material, which is the same as that of Example 1, except that in step (2), the temperature is raised to 800 degrees Celsius and calcined at 800 degrees Celsius for 4 hours.

[0067] Figure 3 This is a scanning electron microscope image of the carbon material prepared in comparative example 1 of the present invention. It can be seen from the image that the material basically maintains the original morphology and structure of ZIF8, and there is un-volatilized zinc element around it.

[0068] Figure 4 This is the nitrogen adsorption-desorption curve of the carbon material prepared in Comparative Example 1 of the present invention. The specific surface area of ​​the material is 87.55 m2 / g, and it is mainly mesoporous. The small specific surface area is mainly due to the precipitation of zinc element in ZIF-8 at 800 degrees Celsius, which causes the pores to be blocked.

[0069] Comparative Example 2

[0070] This comparative example provides a method for preparing a carbon material, which is the same as Example 1, except that the heating rate is adjusted to 5 degrees Celsius per minute.

[0071] Figure 5 This is a scanning electron microscope image of the carbon material prepared in Comparative Example 2 of the present invention. From the image, it can be seen that the material presents a lamellar structure.

[0072] Figure 6 This is the nitrogen adsorption-desorption curve of the carbon material prepared in Comparative Example 2 of the present invention. The specific surface area of ​​the material is 713.79 m2 / g, and the mesopores and micropores are evenly distributed.

[0073] Application Example 1

[0074] The ant nest-shaped carbon material obtained in Example 1 was applied to zinc-iodine button cells for electrochemical testing.

[0075] Take 0.1 g of the ant nest-shaped carbon material prepared in Example 1, mix it with 0.15 g of iodine, put it into a stainless steel reactor with a polytetrafluoroethylene liner, and heat it in a blast oven at 130 degrees Celsius for 5 hours. After heating, take its powder and dry it in an oven at 130 degrees Celsius for 1 hour to remove the residual iodine on the surface to obtain an iodine-loaded carbon material. According to the iodine loading calculation formula of the material, the iodine loading is determined to be 55%. The prepared iodine-loaded carbon material powder, superconducting carbon black and LA133 type water-based binder are mixed in a degassing machine for 2 hours in a mass ratio of 7:2:1, and evenly coated on a circular graphite paper with a diameter of 1 cm, and dried in a vacuum oven at 60 degrees Celsius for 12 hours.

[0076] The dried electrode was used as the positive electrode, the zinc sheet as the negative electrode, and 50 μl of an aqueous solution containing 2 mol ZnSO4 and 0.05 mol potassium iodide as the electrolyte to assemble a button cell. Cyclic voltammetry curve test was performed at a scanning rate of 5 mV / s in the potential window of 0.6-1.6 volts. Figure 7 shown.

[0077] Figure 8 This is the constant current charge and discharge curve of the button battery prepared in Application Example 1 of the present invention; its constant current charge and discharge curves for the first 1-11 cycles at a current density of 1 A / g basically overlap and remain unchanged at 204.8 mAh / g, indicating that the carbon material has good rate performance.

[0078] Fig. 9 The cycle curve of the button battery prepared in Application Example 1 of the present invention at 1 A / g; the ant nest-shaped carbon material has a specific capacity of 206.8 mAh / g at 1 A / g and after 10,000 cycles, the capacity retention rate is 89.9%, showing a long service life potential.

[0079] Application Example 2

[0080] The ant nest-shaped carbon material obtained in Example 2 was applied to zinc-iodine button cells for electrochemical testing.

[0081] Take 0.1 g of the ant nest-shaped carbon material prepared in Example 2, mix it with 0.15 g of iodine, put it into a stainless steel reactor with a polytetrafluoroethylene liner, and heat it in a blast oven at 130 degrees Celsius for 5 hours. After heating, take its powder and dry it in an oven at 130 degrees Celsius for 1 hour to remove the residual iodine on the surface to obtain an iodine-loaded carbon material. According to the iodine loading calculation formula of the material, the iodine loading is determined to be 37.5%. The prepared iodine-loaded carbon material powder, superconducting carbon black and LA133 type water-based binder are mixed in a degassing machine for 2 hours in a mass ratio of 7:2:1, and evenly coated on a circular graphite paper with a diameter of 1 cm, and dried in a vacuum oven at 60 degrees Celsius for 12 hours.

[0082] The dried electrode was used as the positive electrode, the zinc sheet as the negative electrode, and 50 μl of an aqueous solution containing 2 mol ZnSO4 and 0.05 mol potassium iodide as the electrolyte to assemble a button cell. Cyclic voltammetry curve test was performed at a scanning rate of 5 mV / s in the potential window of 0.6-1.6 volts. Fig.10 shown.

[0083] Fig.11 The cycle curve of the button battery prepared in Application Example 2 of the present invention at 1 A / g; the carbon material has a specific capacity of 193.7 mAh / g at 1 A / g and after 10,000 cycles, the capacity retention rate is 76.5%.

[0084] Application Example 3

[0085] The ant nest-shaped carbon material obtained in Example 3 was applied to zinc-iodine button cells for electrochemical testing.

[0086] Take 0.1 g of the ant nest-shaped carbon material prepared in Example 3, mix it with 0.15 g of iodine, put it into a stainless steel reactor with a polytetrafluoroethylene liner, and place it in a blast oven at 130 degrees Celsius for 5 hours. After heating, take its powder and dry it in an oven at 130 degrees Celsius for 1 hour to remove the residual iodine on the surface to obtain an iodine-loaded carbon material. According to the iodine loading calculation formula of the material in the content of the invention, the iodine loading is determined to be 45.8%. The prepared iodine-loaded carbon material powder, superconducting carbon black and LA133 type water-based binder are mixed in a degassing machine for 2 hours in a mass ratio of 7:2:1, and evenly coated on a circular graphite paper with a diameter of 1 cm, and dried in a vacuum oven at 60 degrees Celsius for 12 hours.

[0087] The dried electrode was used as the positive electrode, the zinc sheet as the negative electrode, and 50 μl of an aqueous solution containing 2 mol ZnSO4 and 0.05 mol potassium iodide as the electrolyte to assemble a button cell. Cyclic voltammetry curve test was performed at a scanning rate of 5 mV / s in the potential window of 0.6-1.6 volts. Fig.12 shown.

[0088] Fig.13 The cycle curve of the button battery prepared in Application Example 3 of the present invention at 1A / g; the carbon material has a specific capacity of 187.2 mAh / g at 1A / g and after 10,000 cycles, the capacity retention rate is 82.5%.

[0089] Application Example 4

[0090] The carbon material obtained in Comparative Example 1 was applied to zinc-iodine button cells for electrochemical testing.

[0091] Take 0.1 g of the ant nest-shaped carbon material prepared in Comparative Example 1, mix it evenly with 0.15 g of iodine, put it into a stainless steel reactor with a polytetrafluoroethylene liner, and heat it in a blast oven at 130 degrees Celsius for 5 hours. After heating, take its powder and dry it in an oven at 130 degrees Celsius for 1 hour to remove the residual iodine on the surface, and obtain an iodine-loaded carbon material. According to the iodine loading calculation formula of the material in the content of the invention, the iodine loading is determined to be 17.7%. The prepared iodine-loaded carbon material powder, superconducting carbon black and LA133 type water-based binder are mixed in a degassing machine for 2 hours in a mass ratio of 7:2:1, and evenly coated on a circular graphite paper with a diameter of 1 cm, and dried in a vacuum oven at 60 degrees Celsius for 12 hours.

[0092] The dried electrode was used as the positive electrode, the zinc sheet as the negative electrode, and 50 μl of an aqueous solution containing 2 mol ZnSO4 and 0.05 mol potassium iodide as the electrolyte to assemble a button cell. Cyclic voltammetry curve test was performed at a scanning rate of 5 mV / s in the potential window of 0.6-1.6 volts. Fig.14shown.

[0093] Fig.15 The cycle curve of the button battery prepared in Comparative Example 1 of the present invention at 1 A / g; the carbon material has a specific capacity of 181.3 mAh / g at 1 A / g and after 10,000 cycles, the capacity retention rate is 67.8%.

[0094] Application Example 5

[0095] The carbon material obtained in Comparative Example 2 was applied to zinc-iodine button cells for electrochemical testing.

[0096] Take 0.1 g of the ant nest-shaped carbon material prepared in Comparative Example 2, mix it with 0.15 g of iodine, put it into a stainless steel reactor with a polytetrafluoroethylene liner, and heat it in a blast oven at 130 degrees Celsius for 5 hours. After heating, take its powder and dry it in an oven at 130 degrees Celsius for 1 hour to remove the residual iodine on the surface to obtain an iodine-loaded carbon material. According to the iodine loading calculation formula of the material in the content of the invention, the iodine loading is determined to be 35%. The prepared iodine-loaded carbon material powder, superconducting carbon black and LA133 type water-based binder are mixed in a degassing machine for 2 hours in a mass ratio of 7:2:1, and evenly coated on a circular graphite paper with a diameter of 1 cm, and dried in a vacuum oven at 60 degrees Celsius for 12 hours.

[0097] The dried electrode was used as the positive electrode, the zinc sheet as the negative electrode, and 50 μl of an aqueous solution containing 2 mol ZnSO4 and 0.05 mol potassium iodide as the electrolyte to assemble a button cell. Cyclic voltammetry curve test was performed at a scanning rate of 5 mV / s in the potential window of 0.6-1.6 volts. Fig.16 shown.

[0098] Example 4

[0099] A zinc-iodine soft pack battery comprises the following steps

[0100] Step (1): Take 0.1 g of the ant nest-shaped carbon material prepared in Example 1, mix it evenly with 0.15 g of iodine, and put it into a stainless steel reactor lined with polytetrafluoroethylene, and place it in a blast oven at 130 degrees Celsius to react for 5 hours for iodine sealing. After the heating is completed, take the powder and dry it in an oven at 130 degrees Celsius for 1 hour to remove the residual iodine on the surface to obtain an iodine-loaded carbon material. According to the iodine loading calculation formula of the material in the content of the invention, the iodine loading is determined to be 55%.

[0101] Step (2): LA133 type water-based adhesive and deionized water are sol-formed in a mass ratio of 3:97, and stirred at high speed for 1 hour to prepare glue solution 1 at a stirring speed of 800 rpm;

[0102] Step (3): mixing and grinding the superconducting carbon black and the iodine-sealed ant nest-shaped carbon material, uniformly adding the mixture to the prepared glue solution 1, and stirring at a high speed for 2 hours to obtain a mixture 1, wherein the iodine-loaded carbon material powder, the superconducting carbon black and the LA133 type aqueous binder are mixed in a ratio of 7:2:1;

[0103] Step (4): adjusting the viscosity of the mixture 1 to 1800 MPa.S and the fineness to 15 μm to obtain a positive electrode slurry for a zinc-iodine battery;

[0104] Step (5): evenly coating the zinc-iodine battery positive electrode slurry on the cut graphite paper current collector, drying, and coating to obtain a zinc-iodine battery positive electrode sheet with a width of 60 mm and a length of 70 mm;

[0105] Step (6): Winding the positive electrode sheet and the negative zinc sheet of the zinc-iodine battery with the glass fiber separator in a positive and negative relative manner into a soft-pack battery core, and covering the core with a finishing glue;

[0106] Step (7): Assemble with the aluminum-plastic film that has been pre-punched to a specified depth and cut, and seal the top and sides to form an unfilled soft-pack battery cell; the aluminum-plastic film is divided into two parts, the tank area and the air bag area; the thickness of the aluminum-plastic film is 150μm; the tank area adopts a single-sided punching method, and a pit with one side open is pressed on the dark side. The tank area is divided into upper and lower grooves, which are folded in half and used to place the soft-pack battery cell. The depth of the two grooves is consistent with the thickness of the soft-pack battery cell; the air bag area adopts an aluminum-plastic film with the same specifications and materials as the battery tank, which is a planar structure with the same size as the plane projection size of the battery tank, and is used to contain the gas generated during the battery formation process;

[0107] Step (8): injecting 1.3 ml of an electrolyte containing 2 mol zinc sulfate and 0.05 mol potassium iodide into the uninjected soft-pack battery cell, pre-sealing the top and side edges to form an injected soft-pack battery; pre-sealing the side edges of the airbag area to form an injected soft-pack battery cell;

[0108] Step (9): The liquid-filled soft-pack battery is placed in a static state until the electrolyte is fully infiltrated, and then vented and sealed to form a zinc-iodine soft-pack battery.

[0109] Fig.17 This is an optical photograph of the soft-pack battery prepared in Example 4 of the present invention (the zinc-iodine soft-pack battery obtained in Example 4);

[0110] Fig.18 This is the constant current charge and discharge curve of the soft-pack battery prepared in Example 4 of the present invention; its charge and discharge potential range is 0.6-1.6 volts, and a specific capacity of 260 mAh / g is obtained after charge and discharge tests.

[0111] Fig.19 This is the energy density curve of the soft-pack battery prepared in Example 4 of the present invention; the energy density is 251.6 Wh / kg (calculated based on the mass of the active substance iodine), which is a certain improvement compared to conventional soft-pack batteries.

[0112] Fig. 20 The temperature comparison diagram of the soft-pack battery prepared in Example 4 of the present invention during the discharge process and the traditional soft-pack battery is shown. The temperature of the ordinary soft-pack battery gradually increases with the increase of time during the discharge process, showing a linear increase trend, and the maximum temperature reaches 49 degrees Celsius, while the maximum temperature of the zinc-iodine soft-pack battery is only 37.5 degrees Celsius, which is 11.5 degrees Celsius lower than that of the ordinary soft-pack battery. This is due to the high heat resistance and thermal conductivity of the graphite paper current collector and the application of the aqueous electrolyte, which effectively reduces the temperature of the zinc-iodine soft-pack battery, prevents the risk of fire and explosion, and improves its safety performance.

[0113] The present invention belongs to the technical field of aqueous battery, and discloses a preparation method of an ant nest-shaped carbon material and a zinc-iodine soft pack battery. The preparation method comprises: (1) preparing ZIF-8 material with zinc nitrate hexahydrate and 2-methylimidazole; (2) calcining the material prepared in step (1) to obtain an ant nest-shaped carbon material; the zinc-iodine soft pack battery comprises a zinc foil negative electrode, an ant nest-shaped carbon material positive electrode, a glass fiber separator and an electrolyte; the ant nest-shaped carbon material prepared by the method of the present invention by adjusting the calcination temperature and the heating rate and other processes has a high specific surface area and a rich pore structure, can effectively carry and limit iodine active substances, and improve the effective utilization rate of iodine element; can limit the dissolution and diffusion of the intermediate product polyiodide ion, effectively enhance its cycle performance to only decay by 10.1% after 10,000 times; and the price is low, the preparation method is simple, and the repeatability is high; matching with zinc foil to form a zinc-iodine soft pack battery, using an aqueous electrolyte and a graphite paper current collector, it is not easy to cause dangerous situations such as combustion or explosion. Due to the excellent thermal conductivity and heat resistance of graphite paper, zinc-iodine soft-pack batteries will not experience large-scale short circuits or temperature runaway explosions even in the case of severe local heating, and safety performance is guaranteed; compared with other soft-pack batteries, the application of graphite paper current collectors shows a trend of increasing energy density.

[0114] The invention discloses a preparation method of an ant nest-shaped carbon material and a zinc-iodine soft-pack battery. The ant nest-shaped carbon material prepared by the method of the invention has a high specific surface area and a rich pore structure, can effectively carry and limit iodine active substances, and improve the effective utilization rate of iodine element; the combination of polyiodide and rich pore surface functional groups can inhibit the dissolution and diffusion of iodine and inhibit the shuttle effect; using graphite paper as a current collector instead of the traditional copper / aluminum foil current collector effectively solves the problems of energy density and safety improvement in the current soft-pack battery. Since the graphite paper current collector has the characteristics of low density, high temperature resistance and good thermal conductivity, it can significantly improve the energy density and effectively conduct the heat generated inside the battery; the use of aqueous electrolyte can prevent the occurrence of battery explosion and fire caused by temperature runaway. This provides strong technical support for the future commercial production of graphite paper fluid soft-pack batteries. The results show that the application of graphite paper current collectors and aqueous electrolytes ensures that the battery has high energy density and safety performance, providing technical support for the future commercial production of graphite paper current collector soft-pack batteries.

[0115] The above-mentioned embodiments only express the specific implementation of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. It should be pointed out that for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.

Claims

1. A method for preparing an ant nest-like carbon material, characterized in that: The preparation method comprises: (1) mixing zinc salt and organic ligand in a solvent, stirring or standing at room temperature to synthesize ZIF-8; (2) calcining the ZIF-8 prepared in step (1) at high temperature in an argon atmosphere to obtain an ant nest-like carbon material.

2. The method for preparing an ant nest-shaped carbon material according to claim 1, characterized in that: In step (1), the zinc salt is zinc nitrate hexahydrate; the organic ligand is 2-methylimidazole; the solvent includes methanol; and the room temperature is 25 degrees Celsius.

3. The method for preparing an ant nest-shaped carbon material according to claim 1, characterized in that: In step (1), the zinc salt is 1-4 moles; the organic ligand is 4-8 moles; and the solvent volume is 200-500 ml.

4. The method for preparing an ant nest-shaped carbon material according to claim 1, characterized in that: The molar ratio of the zinc salt to the organic ligand in step (1) is 1:

4.

5. The method for preparing an ant nest-shaped carbon material according to claim 1, characterized in that: The high temperature in step (2) is 900-1000 degrees Celsius.

6. The method for preparing an ant nest-shaped carbon material according to claim 1, characterized in that: The heating rate of the high temperature in step (2) is 2-3 degrees Celsius per minute; and the calcination time is 1-4 hours.

7. A zinc-iodine soft-pack battery, characterized in that: The preparation method thereof comprises the following steps: Step (1): Take the mass ratio of (1:1)-(1: 1.5) The ant nest-shaped carbon material according to any one of claims 1 to 6 is mixed with iodine in a high pressure reactor, and reacted in a blast oven at 100-140 degrees Celsius for 2-6 hours for iodine sealing, thereby obtaining an ant nest-shaped carbon material sealed with iodine; Step (2): Sol-forming LA133 water-based adhesive and deionized water, and stirring at high speed for 1-2 hours to prepare glue solution 1; Step (3): mixing and grinding the superconducting carbon black and the iodine-sealed ant nest-shaped carbon material, uniformly adding the mixture to the prepared glue solution 1, and stirring at a high speed for 1-2 hours to obtain a mixture 1; Step (4): adjusting the viscosity of the mixture 1 to obtain a positive electrode slurry for a zinc-iodine battery; Step (5): evenly coating the zinc-iodine battery positive electrode slurry in step (4) on the cut graphite paper current collector, drying, and completing the coating to obtain a zinc-iodine battery positive electrode sheet; Step (6): Winding the positive electrode sheet and the negative zinc sheet of the zinc-iodine battery with the glass fiber separator in a positive and negative relative manner into a soft-pack battery core, and covering the core with a finishing glue; Step (7): Assemble with the aluminum-plastic film that has been pre-punched to a specified depth and cut, and perform top sealing and side sealing to form an unfilled soft-pack battery cell; Step (8): injecting an electrolyte containing zinc sulfate and potassium iodide into the unfilled soft-pack battery cell, pre-sealing the top and side edges, and forming a liquid-filled soft-pack battery; Step (9): The liquid-filled soft-pack battery is left to stand for a while until the electrolyte is fully infiltrated to form a zinc-iodine soft-pack battery.

8. The zinc-iodine soft-pack battery according to claim 7, characterized in that: In step (2), LA133 type water-based adhesive and deionized water are sol-formed in a mass ratio of 3:

97.

9. The zinc-iodine soft-pack battery according to claim 7, characterized in that: The mass ratio of the LA133 aqueous adhesive in step (2), the superconducting carbon black in step (3), and the iodine-sealed ant nest-shaped carbon material is 7:2:

1.

10. The zinc-iodine soft-pack battery according to claim 7, characterized in that: In step (8), in the electrolyte, the content of zinc sulfate is 2 moles and the content of potassium iodide is 0.05 moles.

Citation Information

Patent Citations

  • Preparation method of binary composite wave-absorbing material

    CN113462356A

  • Iodine-doped derivative porous carbon composite material and preparation method thereof

    CN114132915A

  • High-iodine-loading carbon material composite positive electrode, aqueous zinc ion iodine secondary battery and preparation method

    CN116864603A

  • Preparation method of M-coated N-C catalyst applied to zinc-iodine battery as well as product and application of M-coated N-C catalyst

    CN118198356A